Surface fuel changes after severe disturbances in northern Rocky Mountain ecosystems - Stalling, Chris; Keane, Robert E.; Retzlaff, Molly (Forest ecology and management, 2017)
•Dead foliage is supported in the canopy briefly following severe disturbance.•Increased risk of fire spread/intensity greatest 1–2years following disturbance.•Accumulation of surface fuel loadings do not increase substantially in a decade.•Heavy fuel loads do not accumulate in a decade following fire/insect disturbance. It is generally assumed that severe disturbances predispose damaged forests to high fire hazard by creating heavy fuel loading conditions. Of special concern is the perception that surface fuel loadings become high as recently killed trees deposit foliage and woody material on the ground and that these high fuel loadings may cause abnormally severe fires. This study evaluated effects of severe, exogenous disturbance events, namely fire and beetles, on future fuel conditions through biannual field collections. We measured surface fuel deposition and accumulation rates for a number of forest types after severe wildfires, Douglas-fir beetle outbreaks, and mountain pine beetle outbreaks to quantitatively describe fuel dynamics for up to 10years after the disturbance. Fuel deposition was measured from semi-annual collections of fallen biomass sorted into six fuel components (fallen foliage, twigs, branches, large branches, logs, and all other material) from a network of seven, one meter square litter traps established on 15 sites across the northern Rocky Mountains USA. We also measured fuel loadings of the same six fuel components on each plot every year until the end of the study. Results show that most foliage material fell within the first one to two years after disturbance and surface fuel loadings did not appear to increase substantially at any point during the 10years of this study. Large woody material greater than 75mm diameter was found infrequently in the litter traps. Our results suggest that there is little increase in fire hazard during the first 10years after severe disturbance in the study sites sampled for this study.